Re‐examination of the 1928 Parral, Mexico earthquake (M6.3) using a new multiplatform graphical vectorization and correction software for legacy seismic data. Issue 1 (25th April 2022) - Corona‐Fernández, Raúl Daniel; Santoyo, Miguel Ángel
Abstract: Modern analysis of earthquakes depends on digital time series; however, only about 30% of the timespan of recorded seismicity is available in digital format. During the first half of the 20th century, most of the earthquake ground motions in Mexico were recorded by Wiechert mechanical instruments on smoked paper. In this work, we developed and use Tiitba, a new portable multiplatform graphical user interface (GUI) open‐source software coded on python, to vectorize and correct old analogue seismograms. Using this software, we vectorized the 11/1/1928 Parral (M6.3) earthquake seismograms to obtain the constant time‐interval digitized time series for each component and station of the seismogram. Then, we obtained its source focal mechanism using a genetic algorithm methodology. Also, with an auxiliary Tiitba module, we constructed a SEISAN S‐file to relocate the hypocentre of this earthquake. The obtained relocation is about 125 km south of a recently recorded seismic swarm that occurred in 2013, which has a similar focal mechanism to the one that we obtained in this work. Abstract : Re‐examination of historical earthquakes from legacy seismic data requires reliable vectorization and correction of analog seismograms. Nowadays, computational capabilities allow the development of ad‐hoc programs to perform such analysis. In this work we use Tiitba, our own developed Python based‐software to vectorize, analyze and correct the analog seismograms of the 1928 Parral earthquake towards a focal mechanism redetermination through a Genetic Algorithm method. Also, with an auxiliary Tiitba module, we create a SEISAN S‐file to recalculate the earthquake hypocenter.